Stress Testing at the IMF - Swinburne, Mark (IMF Working Papers; Working Paper ;, 2008)
For almost a decade, the IMF has been using stress tests to identify vulnerabilities across institutions that could undermine the stability of a country's financial system. This working paper focuses on the IMF's experience with stress testing in the Financial Sector Assessment Program (FSAP). It provides background on the nature of an FSAP and the role of macro stress testing within it. It also describes how the methodology of stress testing in FSAPs has been evolving and what are fairly common approaches now being used. Finally, it discusses the main strengths and challenges for future development of macro stress testing in FSAPs and provides an overview of stress testing practice in European FSAPs.